Public enterprise in Ireland: a statistical description and analysis - Sweeney, Paul (Statistical and Social Inquiry Society of Ireland, 1990)
There is much debate on the role of public enterprises, but little analytical work has been done on the subject in Ireland. Fitzgerald (1961), Bristow (1964/65, 1968, 1969 and 1982), Jacobson (1978), the National Economic and Social Council (1980), Dorgan (1984 and 1986), the Joint Oireachtas Committee on State Sponsored Bodies (October, 1986), McDowell (1987), Walsh (1987) and Sweeney (1988a) have undertaken studies, the majority of which have been largely descriptive, and there also have been individual case studies of enterprises, for example, on Aer Lingus (O'Donoghue, 1968/69), Bord na Mona (Bristow and Fell, 1971), the ESB, (Roche, 1978) (Manning and McDowell, 1984), NET (Blackwell et al., 1983). In addition there have been institutional examinations of enterprises, the most important of which are the reports of the Joint Oireachtas Committee on State Sponsored Bodies (JOCSSB) on individual enterprises, and there have been government sponsored consultant examinations, for example, McKinsey on CIE (1971 and 1980), and Fletcher (1971) and Jakobsen (1984) on the ESB.
Read before the Society, 15 February, 1990
Keywords: Public enterprise; Semi-state companies; Employment rates; Profitability; 314.15